Sustainability of Lolium multiflorum L. ‘cajamarquino ecotype’, associated with Trifolium repens L., at three cutting frequencies in the Northern Highlands of Peru - Vallejos Cacho, Romy; Vallejos Fernández, Luis Asunción; Alvarez García, Wuesley Yusmein; Tapia Acosta, Eduardo Alberto; Saldanha Odriozola, Sylvia; Quilcate Pairazaman, Carlos Enrique (MDPI, 2024)
Livestock farming feed in the northern highlands of Peru is based on the association of ryegrass (Lolium multiflorum L.) ecotype cajamarquino–white clover (Trifolium repens L.) Ladino variety, which constantly varies in its agronomic characteristics and nutritional value due to management considerations and its association with the soil and the animal. The objective of this study was to evaluate yield, plant height, growth rate, tillering, tiller number, spikelets, basal diameter in ryegrass, elongation rate, internode length and decline points in clover over one year. Nutritive value was represented by crude protein (CP), neutral detergent fibre (NDF), in vitro digestibility of dry matter (IVDDM) and metabolisable energy (ME) at three cutting frequencies (30, 45 and 60 days). Better yield (5588 kg DM ha) and plant height (47.1 cm) were shown by the 60-day cutting frequency; however, there was no difference (p > 0.05) between the three cutting frequencies in annual yield. There were no differences between the number of tillers and basal diameter. Clover height, elongation rate and internode length were higher at 60 days. The highest CP concentration and the lowest NDF value (p < 0.05) were achieved by clover at 30 and 45 days. Producers should consider the results when deciding when to use this association in dairy cattle feeding.